ANALISIS KELAYAKAN DAN SENSITIVITAS USAHA PEMBIBITAN KRISAN TEKNIK STEK PUCUK (Studi Kasus Penangkar Bibit Krisan di Kakaskasen Dua) - Sudarti ., Sudarti; Femi Hadidjah Elly; Leonardus Ricky Rengkung (Sam Ratulangi University, 2021)
This study aims to analyze the financial feasibility and sensitivity of the chrysanthemum seeding business using shoot cutting techniques if there is a change in seed production, selling price of seeds and cost of seedling production. The research was conducted using a case study method on chrysanthemum breeders with shoot cutting techniques in Kakaskasen Dua from August to October 2020. Data were collected through interviews and field observations. The data analysis usedin this research are financial feasibility analysis with investment criteria of NPV value, Net B/C, IRR, PP and sensitivity analysis. Based on the results of this research, it can be concluded that the chrysanthemum seeding business using shoot cuttings in Kakaskasen Dua is considered profitable, so it is feasible to continue as a solution to meet the demand for chrysanthemum seedlings. The limit for reducing the production of chrysanthemum cuttings that are still tolerable so that businesses do not lose money is 11.77%, the limit for decreasing the selling price of seeds is up to 11.77% and the limit for increasing the cost of producing seeds is up to 19.08%.